Predicting first trimester pregnancy outcome: derivation of a multiple marker test - Senapati, Suneeta; Sammel, Mary D.; Butts, Samantha F.; Takacs, Peter; Chung, Karine; Barnhart, Kurt T. (Fertility and sterility, 2016)
To predict first trimester pregnancy outcome using biomarkers in a multicenter cohort. Case-control study. Three academic centers. Women with pain and bleeding in early pregnancy. Sera from women who were 5–12 weeks' gestational age with ectopic pregnancy (EP), viable intrauterine pregnancy (IUP), and miscarriage/spontaneous abortion (SAB) was analyzed by ELISA and immunoassay for activin A, inhibin A, P, A Disintegrin And Metalloprotease-12, pregnancy-associated plasma protein A (PAPP-A), pregnancy specific B1-glycoprotein (SP1), placental-like growth factor, vascular endothelial growth factor, glycodelin (Glyc), and hCG. Classification trees were developed to optimize sensitivity/specificity for pregnancy location and viability. Area under receiver operating characteristic curve, sensitivity, specificity, and accuracy of first trimester pregnancy outcome. In 230 pregnancies, the combination of trees to maximize sensitivity and specificity resulted in 73% specificity (95% confidence interval (CI) 0.65–0.80) and 31% sensitivity (95% CI 0.21–0.43) for viability. Similar methods had 21% sensitivity (95% CI 0.12–0.32) and 33% specificity (95% CI 0.26–0.41) for location. Activin A, Glyc, and A Disintegrin And Metalloprotease-12 definitively classified pregnancy location in 29% of the sample with 100% accuracy for EP. Progesterone and PAPP-A classified the viability in 61% of the sample with 94% accuracy. Multiple marker panels can distinguish pregnancy location and viability in a subset of women at risk for early pregnancy complications. This strategy of combining markers to maximize sensitivity and specificity results in high accuracy in a subset of subjects. Activin A, ADAM12, and Glyc are the most promising markers for pregnancy location; P and PAPP-A for viability.